UPAYA PENDIDIKAN RAMAH ANAK BAGI PENDIDIKAN AGAMA KRISTEN PASCA-PANDEMIC COVID-19 - Gratia, Yada Putra; Sinambela, Yohana Septina; Wandri Situmorang; Samuel Rido; Pepi Hau Pia (Edukasi : Jurnal Pendidikan Agama Kristen, 2021)
Bullying is a severe issue in the educational world that negatively impacts the physical, emotional, and social well-being of students. This phenomenon includes various forms of intimidation, such as verbal harassment, physical intimidation, spreading rumours, and cyberbullying, which can damage the learning climate and disrupt the educational process. The impact of bullying is highly detrimental to victims, perpetrators, and the school environment as a whole, creating an urgent need for a holistic preventive approach. Bullying prevention involves raising awareness, establishing a positive school culture, effective anti-bullying policies, and active participation from all related parties, including students, teachers, parents, and school staff. Additionally, the role of teachers as counsellors is crucial in supporting the overall development of students. Teachers must have good communication skills, be able to listen empathetically and provide guidance tailored to students' individual needs. By building supportive and trusting relationships, teachers can help students overcome challenges, develop social and emotional skills, and create a safe and inclusive educational environment. Through a comprehensive and collaborative approach, it is hoped that the issue of bullying can be addressed, creating a conducive learning atmosphere for all students..